2007
DOI: 10.1007/s10734-007-9073-5
|View full text |Cite
|
Sign up to set email alerts
|

‘Interdisciplinary strategies’ in U.S. research universities

Abstract: In the context of increasing support for interdisciplinary modes of research, many in the policy, scientific, and academic communities propose that universities should change structurally to reduce the barriers to investigation that involves researchers from multiple disciplines. This paper examines 'interdisciplinary strategies' in U.S. research universities-deliberate efforts to spur collaborative research across traditional departmental and disciplinary boundaries, including the creation and adaptation of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
86
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(95 citation statements)
references
References 35 publications
0
86
0
1
Order By: Relevance
“…In fact, several writers have suggested that discipline focused approaches to SoTL can and should co exist alongside opportunities for interdisciplinary work and exchange (e.g., Fanghanel, 2013;McKinney, 2013). Like wise, respondents to the present survey, echoing the literature about organized research institutes in other fields (Sá, 2007), emphasized the benefits of communicating with in dividuals across departmental boundaries and engaging in interdisciplinary research via their institutes. To this end, the priority areas established for institute scholarship might intentionally and strategically include interdisciplinary inquiry in addition to address ing disciplinary priorities.…”
Section: Developing Priority Areas For Institute Scholarshipmentioning
confidence: 75%
See 1 more Smart Citation
“…In fact, several writers have suggested that discipline focused approaches to SoTL can and should co exist alongside opportunities for interdisciplinary work and exchange (e.g., Fanghanel, 2013;McKinney, 2013). Like wise, respondents to the present survey, echoing the literature about organized research institutes in other fields (Sá, 2007), emphasized the benefits of communicating with in dividuals across departmental boundaries and engaging in interdisciplinary research via their institutes. To this end, the priority areas established for institute scholarship might intentionally and strategically include interdisciplinary inquiry in addition to address ing disciplinary priorities.…”
Section: Developing Priority Areas For Institute Scholarshipmentioning
confidence: 75%
“…Literature discussing organized research units in other fields also emphasizes additional benefits that attach to these units, in clud ing support for interdisciplinarity (Sá, 2007) and for collaborative scholarship (Boardman & Corley, 2008)-priorities that have also been established for SoTL (McKinney, 2013, Macken zie & Meyers, 2012. Nonetheless, with few exceptions (e.g., Hubball, Clarke, & Poole, 2010), there exists little published information about the effective design and manage ment of SoTL institutes specifically, nor about the experiences of scholars affiliated with these bodies.…”
mentioning
confidence: 99%
“…As a result, interdisciplinary characteristics have emerged as a major issue in research and development (R&D) funding and knowledge production (Bruun et al, 2005;Han and Kyung 2011;Huutoniemi et al, 2010;Lee and Choi, 2010;Mansilla, 2005;Van Rijnsoever and Hessels, 2011;Sá, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Critical analysis of law insists on, and recovers, the autonomy of law as a discipline, while at the same time, regarding law as one discipline among others, and the interdisciplinarity of legal studies not as sui generis, but instead as a reflection of interdisciplinarity in all modes of scholarship and teaching. Here critical analysis of law can draw on a growing body of literature on interdisciplinarity in other disciplines and, more generally, as an approach to learning and teaching (Klein 2010;Sá 2008;Moran 2002;Weingart & Stehr 2000), as well as on recent attempts to better appreciate the role of interdisciplinarity in certain aspects of legal studies (for instance, law & society, legal theory, or legal history) (Lavi 2011;Menkel-Meadow 2007;Vick 2004;Tomlins 2000;Balkin 1996).…”
mentioning
confidence: 99%